Static VAr Compensator Control Using Phasor Measurement Unit Feedback Signals for Voltage Stability Improvement in Power Systems - Faris Alsalem; Ayman Faza (Energy Science & Engineering)
ABSTRACT Demand for electric power is constantly increasing, resulting in enormous rapid growth and adding high stress to the grid. The transmission system is a vital part of power systems; however, it is not expanding at the same rate as the demand. Therefore, the grid requires a more capable transmission network to meet growing demand. Flexible Alternating Current Transmission System (FACTS) devices play a crucial role in the efficient and reliable operation of the power systems. They provide reactive power compensation, improving voltage stability, and increasing the transmission capability of existing transmission lines. Static Var Compensators (SVCs), a type of FACTS device, can be effectively used to improve the voltage profile in the system. Furthermore, Phasor measurement units (PMUs) are essential for power system monitoring, control, and protection. Their high data rates make them ideal for accurately measuring electrical signals, including voltage or current, thus providing synchronized measurements throughout the grid. With the increasing complexity of power grids, maintaining voltage stability has emerged as a critical challenge in modern power systems. Traditional SVC control often depends on delayed or indirect measurements, restricting their response time and effectiveness. PMUs provide high‐speed, synchronized data, and their direct integration with SVC controllers for voltage regulation remains underexplored. This study bridges this gap and presents a method for controlling the SVC using a combination of multiple control modes while obtaining real‐time system measurements using PMUs. Results show that our method significantly improves voltage stability, as witnessed by an improved voltage profile and settling time under various disturbances.